Frailty in primary care: challenges, innovations, and future directions - Kristiana Ludlow; Oliver Todd; Natasha Reid; Hakan Yaman (BMC Primary Care, 2023)
Abstract Frailty is one of the biggest challenges to healthy ageing, and yet our understanding and management of frailty is in its infancy. In this editorial we outline challenges, innovations and future directions in frailty research in primary care, and invite contributions to BMC Primary Care’s “Frailty in Primary Care” Collection.